The Utilization Of Historical Materials Of The Dutch Age Of Oil Exploration In Cepu In Historical Study At Smk Migas Cepu - Hanim, Fitriah; Djono, Djono; Susanto, Susanto (Universitas Sebelas Maret, 2020)
History learning in Senior High Schools and Vocational High Schools is carried out almost the same, both obtaining mandatory history with the aim of studying the history of the nation. Meanwhile, studying history in Senior High Schools contains additional material for the history of specialization. The existence of differences in environment, meaning and purpose makes students less interested and meaningful in learning which results in history learning running less optimally. For this reason, this paper aims to make historical learning relevant to the learning field of Vocational Middle School students, one of which is by utilizing local material in areas close to the environment and even the vocational school. One of them is the use of local materials for the Cepu Oil and Gas Vocational Middle School students, namely the history of Dutch oil exploration in Cepu. This study uses a literature study research method, the authors use a humanistic approach to analyze the relevance of learning materials to the learning environment and the interests or vocational of students. The focus of this research is on discussing history learning in Vocational High Schools and the use of historical material on Dutch oil exploration in Cepu as a learning resource. So that studying history will be relevant and meaningful in accordance with the vocational.